2021
DOI: 10.1093/cid/ciaa1744
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin Area Under the Curve–Guided Dosing and Monitoring for Adult and Pediatric Patients With Suspected or Documented Serious Methicillin-Resistant Staphylococcus aureus Infections: Putting the Safety of Our Patients First

Abstract: The revised vancomycin consensus guidelines recommended area under the curve (AUC)–guided dosing/monitoring for patients with serious invasive methicillin-resistant Staphylococcus aureus (MRSA) infections as a measure to minimize vancomycin-associated acute kidney injury (VA-AKI) while maintaining similar effectiveness. Data indicate that the intensity of vancomycin exposure drives VA-AKI risk. Troughs of 15–20 mg/L will ensure an AUC ≥400 mg × hr/L but most patients will have daily AUCs >600. VA-AKI in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…A recent meta-analysis of CT studies also suggested that there is no difference in AKI between CT and MT, and notably most of the included studies had a cephalosporin-based BL [ 16 ]. Second, VAN AUC-guided dosing, which is associated with lower AKI, was implemented at the DMC in 2015 and is consequently more prevalent in POST compared with PRE [ 32 , 33 ]. Third, our institution switched from piperacillin/tazobactam to cefepime as the primary empiric gram-negative agent of choice in 2015.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of CT studies also suggested that there is no difference in AKI between CT and MT, and notably most of the included studies had a cephalosporin-based BL [ 16 ]. Second, VAN AUC-guided dosing, which is associated with lower AKI, was implemented at the DMC in 2015 and is consequently more prevalent in POST compared with PRE [ 32 , 33 ]. Third, our institution switched from piperacillin/tazobactam to cefepime as the primary empiric gram-negative agent of choice in 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the easiest and safest way to achieve this PK target is the use of continuous infusions [ 220 ], with most data suggesting equivalence in outcomes with intermittent dosing [ 84 ]. This dosing strategy may also help to prevent nephrotoxicity [ 221 ] and decrease the emergence of resistant bacteria [ 75 ].…”
Section: Impact Of Dosing Strategies On Outcomesmentioning
confidence: 99%
“…The levels can be used to calculate an elimination rate constant (Ke) and an apparent volume of distribution (Vd), which together equal vancomycin clearance (CLv). Equation (1).…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…When taken at face value, vancomycin troughs are poor surrogates of the area under the curve (AUC) 1 . The revised vancomycin monitoring guidelines recommend targeting an AUC range of 400–600 mg*hr/L for serious methicillin‐resistant Staphylococcus aureus (MRSA) infections 2 …”
Section: What Is Known and Objectivementioning
confidence: 99%
See 1 more Smart Citation